2019
DOI: 10.1021/acsami.8b19180
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Three-Dimensional Nanostructured Conductive Polymer Hydrogels for Energy-Storage Applications

Abstract: Three-dimensional (3D) nanostructured conducting polymer hydrogels represent a group of highperformance electrochemical energy-storage materials. Here, we demonstrate a molecular self-assembly approach toward controlled synthesis of nanostructured polypyrrole (PPy) conducting hydrogels, which was "cross-linked" by a conjugated dopant molecule trypan blue (TB) to form a 3D network with controlled morphology. The protonated TB by ion bonding aligns the free sulfonic acid groups into a certain spatial structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 66 publications
2
59
0
1
Order By: Relevance
“…EIS is a critical technique to study the internal resistance of the electrode and the resistance between the electrode and electrolyte. The equivalent series resistance (ESR) is obtained from the rst intersection with the real axis 40,41. EIS measurements(Fig.…”
mentioning
confidence: 99%
“…EIS is a critical technique to study the internal resistance of the electrode and the resistance between the electrode and electrolyte. The equivalent series resistance (ESR) is obtained from the rst intersection with the real axis 40,41. EIS measurements(Fig.…”
mentioning
confidence: 99%
“…In PAA‐TB‐PPy hydrogel, the TB was not only used for a dopant but also acts as a crosslinker as the electrostatic and hydrogen bonding interaction between TB and PPy. [ 18 ] The possible structure between PAA‐TB‐PPy hydrogels are shown in Figure S1 in the Supporting Information. In the PAA‐TB‐PPy hydrogel system, in addition to the related interactions between PAA and TB, PPy chain is mainly bound through hydrogen bonding and electrostatic interactions with amino groups and sulfonic acid group on TB and hydrogen bonding with carboxyl groups on PAA.…”
Section: Resultsmentioning
confidence: 99%
“…reported a molecular self‐assembly approach toward controlled synthesis of nanostructured PPy hydrogels, in which TB was used as a physical crosslinking agent, it was found that the TB‐doped PPy hydrogel demonstrated excellent electrochemical performance for energy storage application. [ 18 ] However, related studies about TB used in electrochemical fields are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The polymers that made up CPHs mainly include poly(3,4ethylenedioxythiophene) (PEDOT), polythiophene (PTh), polypyrrole (PPy), and polyaniline (PAni), which form into CPHs by constructing covalently or physically crosslinked hydrophilic network . CPHs, synergizing the advantages of hydrogels and organic conductors, exhibit unique electrical, chemical, and mechanical properties, which endow CPHs great potentials in energy storage device, tissue engineering, and different types of sensors …”
Section: Introductionmentioning
confidence: 99%